Pergeseran Peran dan Eksistensi Al-Quran: Studi Living Quran pada Masyarakat Waido, Pidie, Aceh - Bahri, Samsul; Abraar, Muhammad Nuzul (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This study examines the evolving ways in which the community of Waido, Peukan Baro, Pidie, perceives and engages with the Quran. Initially regarded as a sacred text and a source of religious norms, the Quran has undergone a shift in function and role, becoming a practical instrument used in various social and cultural activities. The research adopts the Living Quran model, employing a qualitative approach that incorporates ethnomethodology, anthropology, and phenomenological analysis. The findings reveal a significant transformation in the status and function of the Quran, which now extends beyond serving as a source of religious guidance to being utilized in everyday practices, such as agricultural rituals and conflict resolution through oath-taking. In Waido, the Quran has become an integral part of social and cultural life, transcending its status as a sacred text to function as a symbolic entity with broader social and spiritual significance. These findings provide insights into how local traditions, such as the Keunduri Blang ritual, shape and are shaped by the community's reception and interpretation of the Quran. Abstrak: Penelitian ini mengkaji perubahan cara masyarakat Waido, Peukan Baro, Pidie, dalam mempersepsikan dan memperlakukan Al-Quran. Al-Quran, yang awalnya dipandang sebagai teks suci dan sumber norma keagamaan, telah mengalami perluasan fungsi dan peran, menjadi instrumen praktis yang digunakan dalam berbagai kegiatan sosial dan budaya. Penelitian ini menggunakan model Living Quran, dengan pendekatan kualitatif yang menggabungkan etnometodologi, antropologi, dan analisis fenomenologis. Hasil penelitian menunjukkan adanya perubahan signifikan dalam kedudukan dan fungsi Al-Quran, yang tidak hanya berperan sebagai sumber petunjuk keagamaan, tetapi juga digunakan dalam praktik sehari-hari, seperti ritual pertanian dan penyelesaian konflik melalui sumpah. Di masyarakat Waido, Al-Quran telah menjadi bagian integral dari kehidupan sosial dan budaya, melampaui statusnya sebagai teks suci dengan berfungsi sebagai simbol sakral yang memiliki makna sosial dan spiritual yang lebih luas. Temuan ini menggambarkan bagaimana tradisi lokal, seperti Keunduri Blang, membentuk dan dipengaruhi oleh resepsi serta interpretasi terhadap Al-Quran.